KOMBINASI LIMBAH KELAPA SAWIT DANAMPAS TAHU SEBAGAI MEDIA BUDIDAYA MAGGOT (Hermetia illucens) SALAH SATU ALTERNATIP PAKAN IKAN - Syahrizal Syahrizal; Ediwarman Ediwarman; M. Ridwan (Universitas Batanghari Jambi, 2014)
This experiment aims to determine the effect of the combination of palm oil waste residue / Palm Kernel Meal (PKM) and pulp out as a growth medium for the cultivation and production of maggot (Hermetia illucens) which can be used as an alternative to fish feed. Media culture is a combination of material experiments 4 kg PKM (100%) and pulp out (0%) treatment A, 3 kg PKM (75%) and 1 kg pulp out (25%) treatment B, 2 kg PKM (50%) and 2 kg of pulp out (50%) treatment C, and 1 kg of PKM (25%) and 3 kg of pulp out (75%) treated D. All of these treatments using a container closed the outdoors. Each container treatment added as much as 5.2 liters of fresh water, then stirred evenly. Data were analyzed by ANOVA and LSD test.The results of the analysis of the experiment 21 days for growth are not significantly different (P <0.05). The average value of the best treatment in A (weight 0.18 ± 0.68 g/individul and length 17.26 ± 1.06 mm), followed by treatment B. (weight 0.17 ± 0.68 g/individual and length of 17.07 ± 1.06 mm), C (weight 0.17 ± 0.68 g/individual and 17.04 ± 1.06 mm of length) and the lowest in the D (0.16 ± 0.68 g/individual and 16.98 ± 1.06 mm). While the yield significantly different (P <0.05), the best biomass production of 1.66 ± 0.1/kg for A, in the lowest treatment 0.57±0.13/kg inD.Keywords: organic materials and cultivation maggot